Determinants of Adoption of Improved Stove Technology in Dendi district, West Shoa, Oromia Regional State, Ethiopia - Legesse, Warkaw; Derese, Andinet; Samuel, Tesfaye (American Journal of Human Ecology, 2015)
Biomass is common fuel in Ethiopia and it mainly burned in inefficient open fires and traditional stoves. As a consequence, this leads to massive deforestation, land degradation and desertification.Data was collected from 150 household heads randomly sampled using survey questionnaire and interview checklist. Data collected were analyzed using descriptive statistics and econometric model. Major findings show that family size/household size, age, energy sources, ownership of livestock and proximity to agriculture extension center, health extension center, main road and market services were positively associated with adoption for instance, household size has statistically significant effect for the household to adopt improved stove at 1% level of significance. Similarly, the proximity from household’s home to market services significant effect on the decision of adoption of improved stove at 1% level of statistically significance. Based on the findings, it was concluded that improvement in resource-use efficiency through improved stove is vital however still application is in an infant stage. To enhance adoption of improved stove it was recommended that: all stakeholders (government and development partners) should plan different strategies to its use through demonstrations, posters, and a radio/TV advertisement is vital.